Distinct Gene Expression Patterns of Calcium Channels and Related Signaling Pathways Discovered in Lymphomas - Stanwood, Shawna R.; Chong, Lauren C.; Steidl, Christian; Jefferies, Wilfred A. (Frontiers in Pharmacology, 2022)
Cell surface calcium (Ca2+) channels permit Ca2+ ion influx, with Ca2+ taking part in cellular functions such as proliferation, survival, and activation. The expression of voltage-dependent Ca2+ (CaV) channels may modulate the growth of hematologic cancers. Profile analysis of Ca2+ channels, with a focus on the Ca2+ release-activated Ca2+ (CRAC) and L-type CaV channels, was performed on RNA sequencing data from lymphoma cell lines and samples derived from patients with diffuse large B cell lymphoma (DLBCL). CaV1.2 expression was found to be elevated in classical Hodgkin lymphoma (CHL) cell lines when compared to other B cell lymphoma cell lines. In contrast, CHL exhibited reduced expression of ORAI2 and STIM2. In our differential expression analysis comparing activated B cell-like DLBCL (ABC-DLBCL) and germinal centre B cell-like DLBCL (GCB-DLBCL) patient samples, ABC-DLBCL revealed stronger expression of CaV1.3, whereas CaV1.1, CaV1.2, and CaV1.4 showed greater expression levels in GCB-DLBCL. Interestingly, no differences in ORAI/STIM expression were noted in the patient samples. As Ca2+ is known to bind to calmodulin, leading to calcineurin activation and the passage of nuclear factor of activated T cells (NFAT) to the cell nucleus, pathways for calcineurin, calmodulin, NFAT, and Ca2+ signaling were also analyzed by gene set enrichment analysis. The NFAT and Ca2+ signaling pathways were found to be upregulated in the CHL cell lines relative to other B cell lymphoma cell lines. Furthermore, the calmodulin and Ca2+ signaling pathways were shown to be downregulated in the ABC-DLBCL patient samples. The findings of this study suggest that L-type CaV channels and Ca2+-related pathways could serve as differentiating components for biologic therapies in targeted lymphoma treatments.